Polynomial chaos based rational approximation in linear structural dynamics with parameter uncertainties. (June 2020) - Schneider, Felix; Papaioannou, Iason; Ehre, Max; Straub, Daniel
Highlights: We develop a surrogate model for representing the frequency response of linear structural dynamics systems. The system response is expressed as a ratio of two polynomial chaos expansions with complex coefficients. We propose a regression approach for fitting the coefficients that is completely non-intrusive. We demonstrate effectiveness of the method with a finite element model of a cross-laminated timber plate. Abstract: Surrogate models enable efficient propagation of uncertainties in computationally demanding models of physical systems. We employ surrogate models that draw upon polynomial bases to model the stochastic response of structural dynamics systems. In linear structural dynamics problems, the system response can be described by the frequency response function. It is well known that standard polynomial chaos expansions of the frequency response present slow convergence around system eigenfrequencies, due to the highly nonlinear nature of the frequency response for low damping. To overcome this issue, we develop a rational approximation that expresses the system response as a rational of two polynomials with complex coefficients. To estimate the latter, we propose a regression approach that is non-intrusive and can be easily coupled with existing deterministic solvers. We demonstrate the effectiveness of the proposed method with two examples, a two-degree-of-freedom system and a finite element model of a cross laminated timber plate.